Mohammedan Temple, San Fernando. Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2010)
Photograph of the San Fernando Jama Masjid, Mucurapo Street, San Fernando, founded 1913.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Mosques--Trinidad and Tobago; Buildings--Trinidad and Tobago; Islam--Trinidad and Tobago; Muslims--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--San Fernando; Architecture--Trinidad and Tobago; Architecture, Asian--Trinidad and Tobago; Islamic architecture--Trinidad and Tobago; Minarets--Trinidad and Tobago